2012
DOI: 10.5301/jva.5000091
|View full text |Cite
|
Sign up to set email alerts
|

Thermodilution versus Saline Dilution Method for Vascular Access Blood Flow Measurement in High-Flux and On-Line Hemodiafiltration

Abstract: Our results demonstrate how the saline dilution method was more accurate than thermodilution in the HF and OL-HDF modalities with routinely prescribed parameters. Finally, in this study, advanced age (>65 years old) and peripheral vascular disease were associated with a significantly lower Qa-value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This indirect dilution method detects early fistula dysfunction by the percentage of access recirculation with a diagnostic sensitivity of 81.8% and a specificity of 98.6% [27]. In our previous cross-sectional studies, we concluded that this method offered a good estimation compared with Qa measured with the gold standard Transonic® method in validation conditions, using a high-flux technique with Qb 300 ml/min without OL-HDF [6,28]. For this reason, it is very important not to consider the Kt value obtained during the day of BTM-Qa measurement because it could lead to false-positive conclusions on access function.…”
Section: Discussionmentioning
confidence: 99%
“…This indirect dilution method detects early fistula dysfunction by the percentage of access recirculation with a diagnostic sensitivity of 81.8% and a specificity of 98.6% [27]. In our previous cross-sectional studies, we concluded that this method offered a good estimation compared with Qa measured with the gold standard Transonic® method in validation conditions, using a high-flux technique with Qb 300 ml/min without OL-HDF [6,28]. For this reason, it is very important not to consider the Kt value obtained during the day of BTM-Qa measurement because it could lead to false-positive conclusions on access function.…”
Section: Discussionmentioning
confidence: 99%